1993
DOI: 10.1017/s0003356100006127
|View full text |Cite
|
Sign up to set email alerts
|

Plasma metabolite and hormone concentrations in Friesian calves of low or high genetic merit: effects of sex and age

Abstract: This study investigated the potential use of blood metabolite and hormone concentrations as genetic markers for milk fat production and their possible interactions with sex and age. Two groups of calves, one from the Massey University high breeding index (HBI) line of dairy cattle (seven males, eight females) and the other from the low breeding index (LBI) line (four males, 11 females), were studied at 3-5 months and 7 months of age. The average breeding indices (BI) of the calves based on ancestry BI were 138… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
5
0
3

Year Published

1993
1993
2017
2017

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 28 publications
1
5
0
3
Order By: Relevance
“…Plasma concentrations of glucose and insulin were determined as described by Min, McCutcheon, Mackenzie and Wickham (1993). Plasma progesterone concentrations were analysed by the radioimmunoassay method of Kirkwood, Lapwood, Smith and Anderson (1984) with intra-and interassay coefficients of variation proportionately 0-063 and 0-137 of the mean.…”
Section: Chemical Analysesmentioning
confidence: 99%
“…Plasma concentrations of glucose and insulin were determined as described by Min, McCutcheon, Mackenzie and Wickham (1993). Plasma progesterone concentrations were analysed by the radioimmunoassay method of Kirkwood, Lapwood, Smith and Anderson (1984) with intra-and interassay coefficients of variation proportionately 0-063 and 0-137 of the mean.…”
Section: Chemical Analysesmentioning
confidence: 99%
“…Este fato tambĂ©m Ă© relatado por Kurz e Willett 13 que, adicionalmente afirmaram que os rins assumem tambĂ©m o controle do balanço hidroeletrolĂ­tico. Em razĂŁo disto, a grande maioria dos trabalhos comprovaram a influĂȘncia do fator etĂĄrio sobre os nĂ­veis de urĂ©ia sĂ©rica, principalmente no perĂ­odo neonatal atravĂ©s de uma diminuição em seus valores3,13,14,19 , e mais recentemente20 , refletindo a crescente melhoria da eficiĂȘncia da função renal com o evoluir da idade.A diferenças encontradas na comparação com resultados de outras pesquisas pode ser justificada pela grande sensibilidade dos nĂ­veis de urĂ©ia a fatores de manejo como a nutrição. Segundo Ruppanner et al21 e Quigley e Bernard 22 , os nĂ­veis de urĂ©ia sanguĂ­nea alĂ©m de sofrerem influĂȘncia do fator etĂĄrio tambĂ©m se alteram em função da ingestĂŁo protĂ©ica, concordando com as afirmaçÔes de Lumsden, Mullen e Rowe 23 , que encontraram valores de urĂ©ia sĂ©rica superiores para os animais de um a 14 dias de vida quando comparados aos observados obtidos nesta pesquisa, e Min et al 19 , que estudaram bezerros de trĂȘs a cinco meses e de sete meses de idade por 12 horas.…”
unclassified
“…Many authors investigated the relationship between milk production and the plasma NEFA concentration in fast. The relationship was either positive 18,20 or absent 7,11,12,19,23 . This discrepancy could be due to the low heritability of plasma NEFA concentration 16 .…”
Section: Discussionmentioning
confidence: 99%
“…If some traits were significantly correlated with milk production and could be easily measured in calves, selection to shorten the generation interval and accelerate the rate of genetic improvements might become easier 18,20 . Many authors suggested that milk production traits are associated with plasma metabolite concentrations in fast 7,11,12,[18][19][20]23 . Maximum degree of physiological lipolysis was observed when the energy intake was restricted.…”
Section: Introductionmentioning
confidence: 99%